2014
DOI: 10.1128/iai.01246-13
|View full text |Cite
|
Sign up to set email alerts
|

Functional Roles for C5a and C5aR but Not C5L2 in the Pathogenesis of Human and Experimental Cerebral Malaria

Abstract: fThe host immune response plays an important role in the onset and progression of cerebral malaria (CM). The complement system is an essential component of the innate immune response to malaria, and its activation generates the anaphylatoxin C5a. To test the hypothesis that C5a signaling contributes to the pathogenesis of CM, we investigated a causal role for the C5a receptors C5aR and C5L2 in a mouse model of experimental CM (ECM) induced by Plasmodium berghei ANKA infection, and using a case-control design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…However, in different animal models, the functions of C5aR and C5L2 are controversial. 17,18 Thus, changes in the expression levels of C5aRs need to be linked with disease status. Under physiological conditions, relatively low levels of C5a may accelerate the priming of neutrophils and monocytes, and also activate endothelial cells, supporting efficient natural immune responses in the case of infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, in different animal models, the functions of C5aR and C5L2 are controversial. 17,18 Thus, changes in the expression levels of C5aRs need to be linked with disease status. Under physiological conditions, relatively low levels of C5a may accelerate the priming of neutrophils and monocytes, and also activate endothelial cells, supporting efficient natural immune responses in the case of infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, only C5aR, and not C5L2, is coupled to G proteins and is usually regarded as the major receptor for C5a to exert the proinflammatory property (24). As a result, efforts at targeting C5aR to attenuate inflammatory damage have been most successful (48,49). We have presented convincing evidence that C5 plays a critical role in chlamydial induction of hydrosalpinx.…”
Section: Fig 3 Detection Of C5a In Oviduct Tissues and Sera Of C3mentioning
confidence: 82%
“…This is an area of some contention as another study has reported C5aR deletion, but not deletion of the related receptor C5L2, leads to improved survival and reduced levels of inflammatory molecules leading to lower levels of sequestered parasitised erythrocytes and mononuclear cells, easing the cerebral malaria burden (Kim et al, 2014). C5aR deletion mice also displayed enhanced angiogenic stability and enhanced blood brain barrier integrity, loss of which are hallmarks of cerebral malaria, indicating that C5a-C5aR contribute to the loss (Kim et al, 2014). A similar process is seen in experimental lupus, a disease that can cause neurological symptoms (Jacob et al, 2010(Jacob et al, , 2011Kim et al, 2014).…”
Section: Complement and Cerebral Malariamentioning
confidence: 93%